Possible role of the HMGB1 and RAGE inflammatory pathway in primary sclerosing cholangitis - Sander, Julia; Sauer, Peter; Weiss, Karl Heinz; Gotthardt, Daniel; Rupp, Christian (Clinics and research in hepatology and gastroenterology, 2022)
Background - Activation of the receptor for advanced glycation end products (RAGE) and its ligand High Mobility Group Box Protein 1 (HMGB1), a nuclear protein with proinflammatory properties, has been implicated in several inflammatory disorders. - Objective - To analyse the influence of RAGE and HMGB1 signalling in patients with primary sclerosing cholangitis (PSC). - Methods - Levels of HMGB1 and bile acid in serum and bile samples of 69 PSC patients and 32 controls were measured. Additionally, 640 patients with PSC and other liver diseases were analysed for the gain-of-function RAGE G82S SNP by PCR. Laboratory and clinical parameters were retrieved by chart review. - Results - ELISA analysis showed significantly higher biliary HMGB1 concentrations in PSC patients (n=69, median 124,1 ng/ml) than in the control group (n=32, median 6,85 ng/ml, p<0,001). Median serum HMGB1 (n=22, median 2,4 ng/ml) was significantly lower than median biliary HMGB1 of the concomitant bile samples (n=22, median 151 ng/ml, p =0,001). There was no correlation of biliary HMGB1 levels with laboratory parameters or clinical end points. Analysis of the gain-of-function G82SSNP RAGE SNP in PSC patients showed 8 patients with heterozygote mutant alleles (8/324, 2,5%). Patients carrying the mutation developed more often dominant strictures of the large bile ducts (100.0% vs. 61.3%; p=0.04) and had reduced transplantation-free survival in the mutant allele group (p<0.001). - Conclusions - Biliary HMGB1 levels are elevated in PSC patients compared to controls and a gain-of-function SNP in RAGE is associated with development of dominant strictures and reduced survival in PSC patients.
Available online 14 August 2021
Gesehen am 07.06.2022